Healthy Practices, Social Relationships and Dental Perceptions Among US Dentate Adults - Piya Siriphant, DDS, MPH, PhD; Thomas F. Drury, PhD (Blackwell Synergy, 2005)
This study explored and described the effects of healthy practices and social relationships on dental perceptions among U. S. dentate adults.